Theoretical assessment of energy recovery from Beekeeping waste (Slumgum) - Contreras Bilbao, Diego; Blanco Machin, Einara; Travieso Pedroso, Daniel; Blanco Machín, Adrian [UNESP] (Elsevier, 2022)
An evaluation of the energy potential of organic waste called “slumgum,” generated in the bee-wax industry, is developed. The main objective is to determine whether this waste can be used as fuel to generate the steam required in the plant, considering its combustion in a fluidized bed boiler. Currently, there are no studies in the literature associated with the use of slumgum for energy purposes; only its use for agricultural purposes is studied, thus highlighting the novelty of the present research. The slumgum's main physical–chemical and energy properties are determined, complementing the information available in the literature and mathematical correlations, obtaining a higher heating value of 17,076 MJ/kg in the dry base. An energy balance was made in the boiler, considering a bubbling fluidized bed system's operating conditions. Results show that for typical temperature values in the hearth of 850 °C and excess air of 20%, only 25% of the heat released in combustion is used to generate steam; the rest is lost as sensible heat in the exhaust gases. The plant's steam demand could be fully satisfied using the sensible gases heat, feeding 1.778 kg of slumgum of 8.000 kg produced during the all season, indicating that 77% of the feedstock remain as energy reserve. The proposed process's energy-ecologic-efficiency is 0,8; the economic savings obtained by fuel replacement, taking natural gas as a reference, corresponds to 716 USD per season.
Keywords: Beekeeping waste; Combustion; Energy recovery; Fluidized bed